2023
DOI: 10.3390/su151511541
|View full text |Cite
|
Sign up to set email alerts
|

What Drives People’s Willingness to Adopt Autonomous Vehicles? A Review of Internal and External Factors

Abstract: This article presents a state-of-the-art literature review to understand people’s perceptions and opinions of Autonomous Vehicles and the factors that influence their adoption. A strategic literature search was conducted to select articles for this review. Most of the articles were published since 2015 and they used a household questionnaire survey to collect data. Mostly, they used statistical and econometric methods to evaluate the factors that affect people’s intentions to adopt Autonomous Vehicles. The res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Scholars argue that trust directly impacts acceptance intention while attitudes, perceived usefulness, and perceived ease of use indirectly affect acceptance intention [21]. With further research, some researchers have found that the introduction of autonomous driving technology is not a panacea for all problems [22]. Instead, it is necessary to consider different user needs to provide customized transportation services [23].…”
Section: Impact Of Psychological Factors On Purchase Likelihood For Avsmentioning
confidence: 99%
“…Scholars argue that trust directly impacts acceptance intention while attitudes, perceived usefulness, and perceived ease of use indirectly affect acceptance intention [21]. With further research, some researchers have found that the introduction of autonomous driving technology is not a panacea for all problems [22]. Instead, it is necessary to consider different user needs to provide customized transportation services [23].…”
Section: Impact Of Psychological Factors On Purchase Likelihood For Avsmentioning
confidence: 99%
“…We have made a fair comparison of our proposed method with other existing methods in terms of hardware configuration variations and other parameter variations like speed and memory. We feed a similar quantity (16,384) of input point clouds and OpenPCDet [68] configuration is followed for memory. Our method also shows average results in GPU memory consumption reports, as shown in Table 6.…”
Section: Dfa-sat Efficiencymentioning
confidence: 99%
“…Recent advancements in autonomous driving technology have significantly propelled the development of sustainable smart cities [16][17][18]. Notably, 3D object detection has emerged as a pivotal element within autonomous vehicles, forming the basis for efficient planning and control processes in alignment with smart city principles of optimization and enhancing citizens' quality of life, particularly in ensuring the safe navigation of autonomous vehicles (AVs) [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…While the literature investigating the adoption of automated vehicles is growing, and there are several systematic reviews on the topic (e.g., Rahman and Thill [23] and Nordhoff et al [24]), few studies have explored CAVs within the context of the extended unified theory of acceptance and use of technology (UTAUT2) model, which is considered to be the standard contemporary model to understand the acceptance of technology. We were able to identify two such studies.…”
Section: Introductionmentioning
confidence: 99%